The Hidden Hand of Domestic Labor: Domestic Employers' Work Practices in Chicago, USA - Sternberg, Carolina (Frontiers in Sociology, 2019)
An emergent body of scholarly work exists regarding the manifold dimensions of domestic work, scholarship which draws from various standpoints and discipline traditions. Much existing literature deals specifically with the devaluation of domestic labor. A recent survey conducted in 14 metropolitan areas in the U.S. found that the domestic work industry is profoundly ethnocentric, gendered and racialized, with 23% of domestic workers earning below their state’s mandated minimum wage. In 42 states, it is legal to pay domestic workers below minimum wage, since they are explicitly excluded from the protections of key federal labor laws and standards. In addition, many studies have repeatedly denounced the persistent gendered division of labor in the industry, and in particular have raised concerns about the disproportionate number of women of color in this occupation. Finally, given the private nature of domestic work and the unprotected conditions workers face, studies have pointed to the frequent hostile or even abusive relationships that employers have with their employees. Despite the wealth of research on domestic labor, relatively few studies conducted in the US have focused on the practices of domestic employers. There is also a dearth of research on domestic employment located specifically in the Midwest. The lacuna in this research motivated us to conduct a preliminary study on Midwestern employers’ practices, in particular in Chicago and the surrounding suburbs. We argue that overlooking domestic employers' work practices prevents us from tackling the situations of abuse and disrespect that so frequently occur in this particular work environment.